ABO blood group and risk of glioma: a case control study from Serbia - Azanjac Arsić, Ana; Miletić Drakulić, Svetlana; Vesić, Katarina; Tončev, Gordana (Vojnosanitetski pregled, 2021)
Backgraund/Aim. Gliomas are the most common primary brain tumors and the etiology is unknown. The aim of this study was to investigate possible association between incidence in relation to glioma and certain blood groups. Methods. The case-control study included 100 pathologically confirmed cases of glioma at the Clinical centar of Kragujevac, Serbia, between 2014 and 2015, and 200 age- and sex-matched controls without malignant diseases in personal and family history at the same institution. After signing the informed consent, all patients filled out an epidemiological questionnaire. Results. In the analysis comparing the glioma patients with the control group, a significant association (p < 0.0005) was observed in relation to the blood group AB. Furthermore, it was not observed a significant association in relation to the blood group A (p = 0.070), blood group B (p = 0.256), blood group O (p = 0.768) among the compared groups. Also, in the analysis comparing glioma patients with the control group, a significant association was observed in relation to the years spent in hometown (p = 0.035), changing the place of residence (p = 0.007), the body weight (p = 0.002) and the body mass index (p < 0.0005). Univariate binary logistic regression showed that higher number of years spent in the hometown [odds ratio (OR) 1.011 95% confidence interval (Cl) 1.000–1.023; p = 0.043], increased body weight (OR 0.976 95% Cl 0.959–0.993, p = 0.006) and increased body mass index (OR 0.898 95% Cl 0.839–0.961; p = 0.002) increase the risk of glioma. However, a change of the residence decreases the risk of glioma (OR 0.327 95% Cl 0.147–0.727; p = 0.006). Univariate binary logistic regression analysis revealed that the individuals with group AB were at 3.5-fold increased risk of developing glioma compared to the individuals with other ABO blood groups (OR 3,429 95% Cl 1,83–6,41; p < 0.0005). Also, there was more male patients with glioma with the blood group AB (p = 0.001). Conclusion. In a present study, we demonstrate that individuals with the group AB have an increased risk of developing glioma.
Keywords: glioma; blood group system; risk factors.